Bibliometric Analysis of International Journal of Information Management Indexed in the Scopus Database (2010-2019) - Loorthunayagam, L.; Janen, T.; Ananthasothy, T. (National Conference on Library and Information Science, 2021)
The field of Library and Information Science is emanating as a unique and specialized field as other fields. There are number of journals being published all around the world. Educational institutions and libraries recognize and accept indexed journals in their respective fields. This study evaluates the journals on library and information science using CiteScore as a tool, which is used to evaluate the quality of Scopus indexed journals. Based on this CiteScore, the first ranked journals were selected and analyzed. The journal’s ISSN was used as a search tool and downloaded all the articles published during the period of 2010-2019, in Bibtex and CSV format. All the data were statistically analyzed using Excel and RStudio software. This study identified that International Journal of Information Management (ISSN 0268-4012) was the first ranked journal among the journals indexed in Scopus with the CiteScore of (14.1). During the study period, 956 articles have been published. The highest number of articles was published in the year of 2019. Based on publications, 2782 authors have contributed to this journal, among them 95.33% of the publications were published by multiple authors. Chang, V. was the most productive author (18 articles) and Dwivedi, Y.K had received the highest citations (1321) for 14 publications. The keyword, ‘information management’ was used in 256 articles and the United States was the largest contributor to the publications (22.69%). At the same time, the University of Science and Technology of China published highest number of articles in this journal. This analysis would guide libraries and education institutions on purchasing journals. Moreover, it would guide the researchers of library and information science who do research on these disciplines to select the indexed journals as their publishing platforms.
Keywords: Bibliometric Analysis; Library and Information Science; Journals; Citescore; International Journal of Information Management